The Revitalization of Garapan of Jemblung A Traditional Art Preserved in Blakasuta Studio in Banyumas Regency - Pangestika, Nurratri Widya; Wadiyo, Wadiyo; Rokhmat, Nur (Universitas Negeri Semarang, 2019)
Jemblung is a traditional arts developed in Banyumas regency. Modernization has made the society have less interest in preserving the tradition. Hence, this research aims to analyze the revitalization of Jemblung by Blakasuta studio in Banyumas regency. The researcher employed qualitative interpretative method along with interdisciplinary approach for this research. The discipline of this research mainly concerns on ethnomusicology. The collection for the research data consist of observation, interview, and documentation. The validation of the data was through source triangulation. The analysis for the finding started from data collection, reduction, clarification, conclusion, and selective interpretation. The findings showed that the revitalization of Jemblung covers the ideas, materials, creators, facilities, consideration, reconstruction, refunctionalization, reformation, representation, reinterpretation, and reorientation. This research implies that the revitalization of Jemblung is a form of appreciation of traditional arts by Blakasuta studio. The studio continuously holds traditional arts preservation to minimize the effect of modernization. It is a challenge for the studio and the appreciators to consistently promote and perform traditional arts in a more creative way amongst Banyumas community.